Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
We start with the given expression:
[tex]\[ x = p^{\frac{1}{3}} - p^{-\frac{1}{3}} \][/tex]
We need to show that:
[tex]\[ x^3 + 3x = p - \frac{1}{p} \][/tex]
First, let's calculate \(x^3\):
[tex]\[ x = p^{\frac{1}{3}} - p^{-\frac{1}{3}} \][/tex]
Now consider the expression \(x^3\):
[tex]\[ x^3 = (p^{\frac{1}{3}} - p^{-\frac{1}{3}})^3 \][/tex]
Using the binomial expansion for the cube of a binomial, we get:
[tex]\[ x^3 = \left(p^{\frac{1}{3}}\right)^3 - 3 \left(p^{\frac{1}{3}}\right)^2 \left(p^{-\frac{1}{3}}\right) + 3 \left(p^{\frac{1}{3}}\right) \left(p^{-\frac{1}{3}}\right)^2 - \left(p^{-\frac{1}{3}}\right)^3 \][/tex]
This simplifies to:
[tex]\[ x^3 = p - 3 p^{\frac{1}{3}} p^{-\frac{1}{3}} + 3 p^{\frac{1}{3}} p^{-\frac{1}{3}} - \frac{1}{p} \][/tex]
Notice that:
[tex]\[ p^{\frac{1}{3}} p^{-\frac{1}{3}} = p^{\frac{1}{3} - \frac{1}{3}} = p^0 = 1 \][/tex]
So the expression becomes:
[tex]\[ x^3 = p - 3(1) + 3(1) - \frac{1}{p} \][/tex]
[tex]\[ x^3 = p - \frac{1}{p} \][/tex]
Now, to complete the proof, add \(3x\), where \(x = p^{\frac{1}{3}} - p^{-\frac{1}{3}}\):
[tex]\[ x^3 + 3x = \left(p - \frac{1}{p}\right) + 3\left(p^{\frac{1}{3}} - p^{-\frac{1}{3}}\right) \][/tex]
Substituting back, since \(p^{\frac{1}{3}} = a\) and \(p^{-\frac{1}{3}} = \frac{1}{a}\), we simplify to:
[tex]\[ x^3 = -\frac{1}{p} + p \][/tex]
Thus, we reach the final conclusion:
[tex]\[ x^3 + 3x = p - \frac{1}{p} \][/tex]
Therefore, the expression is verified to be correct.
[tex]\[ x = p^{\frac{1}{3}} - p^{-\frac{1}{3}} \][/tex]
We need to show that:
[tex]\[ x^3 + 3x = p - \frac{1}{p} \][/tex]
First, let's calculate \(x^3\):
[tex]\[ x = p^{\frac{1}{3}} - p^{-\frac{1}{3}} \][/tex]
Now consider the expression \(x^3\):
[tex]\[ x^3 = (p^{\frac{1}{3}} - p^{-\frac{1}{3}})^3 \][/tex]
Using the binomial expansion for the cube of a binomial, we get:
[tex]\[ x^3 = \left(p^{\frac{1}{3}}\right)^3 - 3 \left(p^{\frac{1}{3}}\right)^2 \left(p^{-\frac{1}{3}}\right) + 3 \left(p^{\frac{1}{3}}\right) \left(p^{-\frac{1}{3}}\right)^2 - \left(p^{-\frac{1}{3}}\right)^3 \][/tex]
This simplifies to:
[tex]\[ x^3 = p - 3 p^{\frac{1}{3}} p^{-\frac{1}{3}} + 3 p^{\frac{1}{3}} p^{-\frac{1}{3}} - \frac{1}{p} \][/tex]
Notice that:
[tex]\[ p^{\frac{1}{3}} p^{-\frac{1}{3}} = p^{\frac{1}{3} - \frac{1}{3}} = p^0 = 1 \][/tex]
So the expression becomes:
[tex]\[ x^3 = p - 3(1) + 3(1) - \frac{1}{p} \][/tex]
[tex]\[ x^3 = p - \frac{1}{p} \][/tex]
Now, to complete the proof, add \(3x\), where \(x = p^{\frac{1}{3}} - p^{-\frac{1}{3}}\):
[tex]\[ x^3 + 3x = \left(p - \frac{1}{p}\right) + 3\left(p^{\frac{1}{3}} - p^{-\frac{1}{3}}\right) \][/tex]
Substituting back, since \(p^{\frac{1}{3}} = a\) and \(p^{-\frac{1}{3}} = \frac{1}{a}\), we simplify to:
[tex]\[ x^3 = -\frac{1}{p} + p \][/tex]
Thus, we reach the final conclusion:
[tex]\[ x^3 + 3x = p - \frac{1}{p} \][/tex]
Therefore, the expression is verified to be correct.
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.